Rwanda's Resiliency During the Coronavirus Disease Pandemic - Louis, Elizabeth Farrah; Eugene, Dominique; Ingabire, Willy Chrysostome; Isano, Sandra; Blanc, Judite (Frontiers in Psychiatry, 2022)
The coronavirus disease (COVID-19) pandemic has illustrated the wide range of preventative measures and responsive strategies of low- and middle-income countries (LMICs). LMICs have implemented lessons learned from previous periods of epidemics and uncertainties. Rwanda’s pre-existing decentralized healthcare and mental health system which are in response to the mental health distress from the 1994 genocide, continues to be a formidable system that collaborate and combine efforts to address people’s mental health needs. COVID-19 has heightened or exacerbated people’s mental health within the country. Rwandans have been exposed to and endured adversities, yet their cultural forms of resilience serve as a mental health protective factor to also overcome COVID-19. Nonetheless, Rwanda has engaged in interventions targeting public safety, social and economic protection that specifically address vulnerable communities’ mental health needs. Lessons from preparedness for the Ebola virus disease (EVD) epidemic has contributed to Rwanda’s organization and approach to combating COVID-19. Policies and best practices that were enacted during the EVD outbreak have guided Rwanda’s response within the healthcare and mental health system. Coincidentally, this outbreak emerged during the 26th commemoration of the 1994 genocide against the Tutsi. Although for the first-time post genocide, Rwanda was not able to engage in public traditional forms of collective mourning and community healing, evidence of Rwandans’ resilient spirit is demonstrated. Community resilience has been an interwoven cultural framework that has guided Rwandans in past challenges and is evident now. Rwanda’s resilience throughout this pandemic remains through ongoing psychoeducation, community awareness of mental health concerns, collective messages of highlighting mental health support, and solidarity. The global community can gain knowledge from Rwanda’s learned lessons of their past which has positioned itself to stand on its resilient values in times of uncertainty such as COVID-19 and endeavor to overcome through national cohesion.